Proximate Composition, Mineral Contents and the effects of Sodium Sulphate Salts on Emulsion Capacity and Stability of Mushroom Species obtained from Nigeria - Abulude, Francis Olawale; Ndamitso, Mohammed Mohammed; Akinnusotu, Akinyinka; Elisha, J. J.; Makinde, Olatunde Elubode (Iraqi Journal of Science, 2018)
The proximate composition, mineral contents and the effects of sodium sulphate salts on emulsion capacity (EC) and stability (ES) of mushroom species M1 – Lentinus subnudus Berk, M2 – Chlorophyllum molybditis, M3 – Volvariella esculenta, M4 – Coprinus tramentarius, M5 – Pleurotus ostreatus Jacq, M6 – Termitomyces microcarpus, and M7 – Pleurotus pulmonarius obtained from Nigeria were investigated using standard methods for analyses. The mean of some of the results is: Crude protein: 9.1±0.15 -13.80±0.15%, Crude fibre: 4.15±0.02 – 7.08±0.59%, Na: 177±2.56 – 910±2.56 mg/100 g, P: 480±2.31 – 884±2.43 mg/100 g and Cu: 0.23±0.23 – 0.23±0.23 mg/100 g. In the study, EC and ES were affected by different salt concentrations. In water, the EC results varied from 76.26±20.17 (M2) to 85.70 ± 20.17% (M7) and significantly differed from one another at p > 0.05. The EC of samples in different salt concentrations ranged as follows: 64.48 -86.18, 68.18 - 75.10, 67.18 - 74.51, and 61.48 -75.01% at 2, 4, 6, 8% of the salt concentrations respectively. Salt applications gave lowest ES and EC. These results indicated the interaction between the oil, salt solutions, the mushroom samples, and the blender used to form the emulsions. In stable ES, the interfacial area did not change with time. Consequently, such emulsions have a constant turbidity. In this report, it was observed that coalescence and oiling-off caused an irreversible reduction in the interfacial area. In conclusion, the good emulsifying capacity and stability showed the usefulness of the samples in the food industries and formulations.